Are Emissions of Black Carbon from Gasoline Vehicles Underestimated? Insights from Near and On-Road Measurements - Liggio, John; Gordon, Mark; Smallwood, Gregory; Li, Shao-Meng; Stroud, Craig; Staebler, Ralf; Lu, Gang; Lee, Patrick; Taylor, Brett; Brook, Jeffrey R. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2012)
Measurements of black carbon (BC) with a high-sensitivity laser-induced incandescence (HS-LII) instrument and a single particle soot photometer (SP2) were conducted upwind, downwind, and while driving on a highway dominated by gasoline vehicles. The results are used with concurrent CO2 measurements to derive fuel-based BC emission factors for real-world average fleet and heavy-duty diesel vehicles separately. The derived emission factors from both instruments are compared, and a low SP2 bias (relative to the HS-LII) is found to be caused by a BC mass mode diameter less than 75 nm, that is most prominent with the gasoline fleet but is not present in the heavy-duty diesel vehicle exhaust on the highway. Results from both the LII and the SP2 demonstrate that the BC emission factors from gasoline vehicles are at least a factor of 2 higher than previous North American measurements, and a factor of 9 higher than currently used emission inventories in Canada, derived with the MOBILE 6.2C model. Conversely, the measured BC emission factor for heavy-duty diesel vehicles is in reasonable agreement with previous measurements. The results suggest that greater attention must be paid to black carbon from gasoline engines to obtain a full understanding of the impact of black carbon on air quality and climate and to devise appropriate mitigation strategies.